PENGARUH PUPUK HAYATI BERBASIS MIKORIZA ARBUSKULA TERHADAP PENINGKATAN P TERSEDIA DAN PERTUMBUHAN TANAMAN NANAS (Ananas Comosus (L.) Merr) PADA TANAH MASAM - Dedi Sutrisno; Zaenal Kusuma; Priyo Cahyono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The purpose of this research was to analyze the effect of mycorrhiza based biofertilizer on the availability of P on acid soils and pineapple plant growth. The research was conducted in green hause owned by PT. Great Giant Pineapple, Central Lampung District. The treatments were four doses of Rhizagold biological fertilizer (10, 30, 50, and 70 g / seeds), and 1 control (without Rhizagold biological fertilizer). Five treatments were arranged in a completely randomized design with three replications. Observations were done destructively five times to produce 75 units of experiments. The results showed that the application of mycorrhizal based biochemical fertilizers did not give significant effect on all pineapple plant growth parameters and did not give significant effect on soil pH parameter, P-total, only gave significant effect on P-available. A dose of 30 g seedlings-1 showed the best dose to increase P availability on soil.